Mesoscopic and microscopic aspects of the hypoglossal nerve - Piffer, C. R.; Zorzetto, N. L. (My University, 1982)
Mesoscopic observations on the hypoglossal nerve at the level of the superior portion of the hypoglossal canal, show that this nerve is separated by bundles, which are attached to the wall of the venous plexus of the hypoglossal canal by means of numerous fibrous septum disposed transversaly to the lumen of the canal. The union of the bundles constituting the trunk of the hypoglossal nerve only occurs near this emergency of the base skull through of the hypoglossal canal. One of this nervous bundless describes stretch adhesive to the wall of the venous plexus of the hypoglossal canal, while the others are disposed centrally to the lumen of the canal. The central bundle and the fibrous septum delimit the vascular compartments of the venous plexus of the hypoglossal canal. Microscopically, connective sheaths around the nervous bundles composed of fascicles of cricular, oblique, longitudinal collagenic fibers were observed.